Transmission of Mobile Colistin Resistance (mcr-1) by Duodenoscope. (11th September 2018) - Shenoy, Erica S; Pierce, Virginia M; Walters, Maroya Spalding; Moulton-Meissner, Heather; Lawsin, Adrian; Lonsway, David; Shugart, Alicia; McAllister, Gillian; Halpin, Alison Laufer; Zambrano-Gonzalez, Alejandra; Ryan, Erin E; Suslak, Dolores; et al.
Abstract : The first healthcare-associated transmission of mcr -1 in the United States was associated with shared exposure to a duodenoscope, despite implementation of updated reprocessing instructions and supplemental measures; this represents the first documented duodenoscope-linked transmission since publication of updated reprocessing guidelines. Abstract: Background: Clinicians increasingly utilize polymyxins for treatment of serious infections caused by multidrug-resistant gram-negative bacteria. Emergence of plasmid-mediated, mobile colistin resistance genes creates potential for rapid spread of polymyxin resistance. We investigated the possible transmission of Klebsiella pneumoniae carrying mcr -1 via duodenoscope and report the first documented healthcare transmission of mcr -1–harboring bacteria in the United States. Methods: A field investigation, including screening targeted high-risk groups, evaluation of the duodenoscope, and genome sequencing of isolated organisms, was conducted. The study site included a tertiary care academic health center in Boston, Massachusetts, and extended to community locations in New England. Results: Two patients had highly related mcr -1–positive K. pneumoniae isolated from clinical cultures; a duodenoscope was the only identified epidemiological link. Screening tests for mcr -1 in 20 healthcare contacts and 2 household contacts were negative. Klebsiella pneumoniae and Escherichia coli were recovered from the duodenoscope; neither carried mcr -1. Evaluation of the duodenoscope identified intrusion of biomaterial under the sealed distal cap; devices were recalled to repair this defect. Conclusions: We identified transmission of mcr -1 in a United States acute care hospital that likely occurred via duodenoscope despite no identifiable breaches in reprocessing or infection control practices. Duodenoscope design flaws leading to transmission of multidrug-resistant organsisms persist despite recent initiatives to improve device safety. Reliable detection of colistin resistance is currently challenging for clinical laboratories, particularly given the absence of a US Food and Drug Administration–cleared test; improved clinical laboratory capacity for colistin susceptibility testing is needed to prevent the spread of mcr -carrying bacteria in healthcare settings.